Psycholinguistics in 21st Century Arabic Language Learning - Nafi'ah, Hafidzotun; Setiyawan, Agung (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This research is motivated by Arabic language learning activities which cannot be separated from language activities. Therefore, learning Arabic is not enough just linguistics, but also needs to study mental state or mind, namely psychology. The science of psycholinguistics was born, which is a combination of language and mental science. This research uses a type of library research, the data was analyzed using content analysis. The findings of this study show that psycholinguistics covers language learning strategies as well as the phenomena of language acquisition and learning. Similar to this, learning Arabic involves adhering to linguistic, psychological, and educational principles. These three tenets serve as the interface between psycholinguistics and language acquisition. It is intended that this study would assist teachers in enhancing the Arabic language acquisition process.